Respuesta :
The answer is f(x)=x²+2x when evaluated with -3 gives you the value of 3
Let's check all functions.
1. The function f(x)=x²+2x when evaluated with 3 gives you the value of 3:
Evaluated with x means that x = 3.
f(3) = 3² + 2 * 3 = 9 + 6 = 15
15 ≠ 3, so, this is not correct.
2. f(x)=x²-3x when evaulated with -3 give you the value of 3
Evaluated with -3 means that x = -3.
(f-3) = (-3)² - 3 * (-3) = 9 + 9 = 18
18 ≠ 3, so, this is not correct.
3. f(x)=x²+2x when evaluated with -3 gives you the value of 3
Evaluated with -3 means that x = -3.
f(-3) = (-3)² + 2 * (-3) = 9 - 6 = 3
3 = 3, so this is correct.
4. f(x)=x²-3x when evaluated with -3 gives you the value of 3
Evaluated with 3 means that x = 3.
f(3) = (3)² - 3 * 3 = 9 - 9 = 0
0 ≠ 3, so this is not correct.
Let's check all functions.
1. The function f(x)=x²+2x when evaluated with 3 gives you the value of 3:
Evaluated with x means that x = 3.
f(3) = 3² + 2 * 3 = 9 + 6 = 15
15 ≠ 3, so, this is not correct.
2. f(x)=x²-3x when evaulated with -3 give you the value of 3
Evaluated with -3 means that x = -3.
(f-3) = (-3)² - 3 * (-3) = 9 + 9 = 18
18 ≠ 3, so, this is not correct.
3. f(x)=x²+2x when evaluated with -3 gives you the value of 3
Evaluated with -3 means that x = -3.
f(-3) = (-3)² + 2 * (-3) = 9 - 6 = 3
3 = 3, so this is correct.
4. f(x)=x²-3x when evaluated with -3 gives you the value of 3
Evaluated with 3 means that x = 3.
f(3) = (3)² - 3 * 3 = 9 - 9 = 0
0 ≠ 3, so this is not correct.
Stan evaluated a function with a value and got 3 as the result. He wrote the entire process as a sentence:
The function [ [tex]f(x) = x^{2} +2[/tex] ]
when evaluated with [ 3 ]
gives the value 3.